Kekuatan Retensi Siswa SMA Kelas X dalam Pembelajaran Fisika pada Pokok Bahasan Momentum dan Impuls Menggunakan Lembar Kerja Siswa Berbasis Mind Mapping - Nafida Nur Hasanah; Supeno Supeno; Sri Wahyuni (Program Studi Magister Pendidikan IPA FKIP Universitas Jember Bekerjasama dengan Perkumpulan Pendidik IPA Indonesia (PPII), 2017)
Retention is one of the important factors of a lesson. Retention or memory can be trained to students one using worksheet based on mind mapping. The purpose of this study to determined the students strength of retention after using worksheet based on mind mapping in momentum and impulse matter for students grade X senior high school. Before worksheet based on mind mapping is used in the learning process it must go through a validation process. Worksheet based on mind mapping categorized is valid that worksheet based on mind mapping can be used. The high degree of retention determined by compared the result of second posttest and first posstest. Based on data obtained, worksheet based on mind mapping in momentum and impulse matter for students grade X senior high school student retention results obtained 85.5%, which means retention of students categorized as high. Keywords: worksheet, mind mapping, retention